2014
DOI: 10.3892/ol.2014.2005
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced antitumor effects of low-frequency ultrasound and microbubbles in combination with simvastatin by downregulating caveolin-1 in prostatic DU145 cells

Abstract: Advanced prostate cancer is difficult to treat due to androgen resistance, its deep location and blood tumor barriers. Low-frequency ultrasound (LFU) has potential clinical applications in the treatment of prostate cancer due to its strong penetrability and high sensitivity towards tumor cells. Simvastatin has often been administered as a preventive agent in prostate tumors. The aim of the present study was to investigate the enhanced effects of LFU and microbubbles in combination with simvastatin, in inhibiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 27 publications
0
7
0
1
Order By: Relevance
“…The role of the sonoporation effect in targeted drug release and gene therapy has been demonstrated in animal experiments ( 42 - 44 ). This technique is a promising approach for increasing drug and gene delivery efficiency ( 38 , 45 - 47 ). The primary objective of this study was to explore the safety of ultrasound combined with microbubbles in enhancing the chemotherapeutic sensitivity of malignant tumors in the digestive system.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the sonoporation effect in targeted drug release and gene therapy has been demonstrated in animal experiments ( 42 - 44 ). This technique is a promising approach for increasing drug and gene delivery efficiency ( 38 , 45 - 47 ). The primary objective of this study was to explore the safety of ultrasound combined with microbubbles in enhancing the chemotherapeutic sensitivity of malignant tumors in the digestive system.…”
Section: Discussionmentioning
confidence: 99%
“…The biological influence of LFU and microbubbles on cancer cells is dependent on the microbubble density, ultrasound intensity and irradiation time ( 34 , 35 ). Generally, a pilot experiment should be prepared to debug the optimized ultrasound parameters, so as to induce cell apoptosis to the maximum extent ( 36 , 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…Tabuchi et al (23) observed that 193 genes were downregulated and 201 were upregulated in tumor cells following irradiation by low-frequency ultrasound. These genes are associated with cell growth, proliferation, apoptosis, movement, polymorphism and death (24).…”
Section: Discussionmentioning
confidence: 99%